2017
DOI: 10.1148/radiol.2017162128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rectal Tumors with Shear-Wave Elastography before Surgery: Comparison with Endorectal US

Abstract: Purpose To compare the value of endorectal ultrasonography (US) with shear-wave elastography (SWE) in staging rectal tumors before surgery. Materials and Methods This prospective study was approved by the institutional review board and written informed consent was obtained. In a pilot cohort from April 2015 to January 2016, 70 patients with rectal adenocarcinomas and/or adenomas confirmed with histopathologic examination underwent both endorectal US and SWE. Tumor stiffness and three regions of reference backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
19
0
1
Order By: Relevance
“…The literature search identified 913 abstracts, of which 35 were judged relevant for full assessment. After data extraction, 11 articles met the inclusion criteria and were included in the meta-analysis [12,[20][21][22][23][24][25][26][27][28][29]. The remaining articles did not meet the inclusion criteria and were excluded (Fig.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…The literature search identified 913 abstracts, of which 35 were judged relevant for full assessment. After data extraction, 11 articles met the inclusion criteria and were included in the meta-analysis [12,[20][21][22][23][24][25][26][27][28][29]. The remaining articles did not meet the inclusion criteria and were excluded (Fig.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Another group found good correlation between diffusion-weighted MR imaging which is associated with fibrosis, and SWE of malignant rectal tumors [229]. Another study assessed the performance of ERUS for rectal tumors using SWE using an 8 MHz endorectal transducer, finding that the tumor stiffness measurements corresponded accurately to the pathological tumor T-stage and diagnostic accuracy of tumor staging improved from 76.7 % to 93.3 % [230].…”
Section: Characterization and Staging Of Rectal Tumorsmentioning
confidence: 98%
“…It was first used in GI diseases in 2013 by Dillman et al (10), who conducted a Crohn's disease animal model. Several studies have reported the value of using SWE, especially in inflammatory bowel disease (IBD) and rectal neoplasms (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For instance, it has proven effective in the differentiation of fibrotic from inflammatory strictures in Crohn's disease (14,18) and in assessing and staging rectal tumors (12,13,15).…”
Section: Introductionmentioning
confidence: 99%